2017
DOI: 10.1038/nature24279
|View full text |Cite
|
Sign up to set email alerts
|

Role of stacking disorder in ice nucleation

Abstract: The freezing of water affects the processes that determine Earth's climate. Therefore, accurate weather and climate forecasts hinge on good predictions of ice nucleation rates. Such rate predictions are based on extrapolations using classical nucleation theory, which assumes that the structure of nanometre-sized ice crystallites corresponds to that of hexagonal ice, the thermodynamically stable form of bulk ice. However, simulations with various water models find that ice nucleated and grown under atmospheric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
252
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(274 citation statements)
references
References 67 publications
21
252
1
Order By: Relevance
“…Below about 200 K, however, water may be encountered in the metastable cubic form ice I c (e.g., Hobbs, 1974). Recently, studies using diffraction measurements and numerical simulations showed that samples were not composed of pure cubic ice, but rather exhibited crystalline sequences of cubic ice interlaced with sequences of hexagonal ice (e.g., Hudait et al, 2016;Kuhs et al, 2012;Lupi et al, 2017;Malkin et al, 2015;Shallcross and Carpenter, 1957;Thürmer and Nie, 2013). This ice polymorph has been termed stacking disordered ice I sd .…”
Section: Comparison To Literature Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Below about 200 K, however, water may be encountered in the metastable cubic form ice I c (e.g., Hobbs, 1974). Recently, studies using diffraction measurements and numerical simulations showed that samples were not composed of pure cubic ice, but rather exhibited crystalline sequences of cubic ice interlaced with sequences of hexagonal ice (e.g., Hudait et al, 2016;Kuhs et al, 2012;Lupi et al, 2017;Malkin et al, 2015;Shallcross and Carpenter, 1957;Thürmer and Nie, 2013). This ice polymorph has been termed stacking disordered ice I sd .…”
Section: Comparison To Literature Datamentioning
confidence: 99%
“…Here, k is the Boltzmann constant, T is the temperature, ν is the molecular volume and σ is the ice-vapor surface tension of the crystalline ice. We assume that the crystalline nano-grains are composed of ice I sd as supported by model studies (Lupi et al, 2017) and X-ray diffraction experiments (Morishige et al, 2009). Since the surface tension of hexagonal and cubic ice are assumed to be very similar, we used the surface tension parameterization of hexagonal ice for ice I sd (σ sd = 0.001 Hale and Plummer, 1974) and assumed an uncertainty of 10 %.…”
Section: The Effect Of Nano-crystalline Ice On the Vapor Pressurementioning
confidence: 99%
“…On the basis of quantum mechanical calculations Engel et al (2015) have suggested that the anharmonic vibrational energies favour the hexagonal form as a consequence of differences in the fourth nearest-neighbour protons, related to the occurrence of the topologically different boat and chair forms of the sixmembered water rings in cubic and hexagonal ice. Still, as nucleation (and growth) for supercooled water is kinetically controlled, freezing may well start also with a cubic or a stacking-disordered nucleus (Lupi et al, 2017). The subsequent growth appears experimentally to follow a fast s ¼ 2 Markov chain prescription, before any annealing has time to set in for temperatures below approximately 240 K. It is noteworthy that branching (twinning) has been observed for a significant percentage of snow crystals formed at temperatures higher than about 238 K (Kajikawa et al, 1980), which likely have formed from a cubic (or stacking-faulty) nucleus growing along directions separated by the octahedral angle of 70.53 (i.e.…”
Section: Markov Processes In Relation To the Growth Physics Of Stackimentioning
confidence: 99%
“…Recently, this attention has been motivated by the significant role played by the surface melting of ice in many natural phenomena such as snow and ice disaster and melting glaciers. As a result, the solid-liquid phase transition of water has been the subject of numerous experimental and theoretical investigations [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%